ETHNIC IDENTITY VIS-À-VIS OTHER-GROUP ORIENTATION OF ETHNIC CHINESE IN MALAYSIA - Ting, Su Hie; Ting, Su Lin (Katibeh-ILCRG, 2020)
The study examined the ethnic identity and other-group orientation of ethnic Chinese in Malaysia. The data were collected from 504 Chinese respondents (252 students, 252 parents) using Phinney’s (1992) Multiethnic Identity Measure. The results showed that the parents had a stronger ethnic identity than their children (parents, M=2.91; children, M=2.78). For both groups, the mean scores for affirmation and belonging were the highest among the four ethnic identity components, and the ethnic identity achievement mean scores were the lowest. The results indicate that the Foochow Chinese respondents had a foreclosed identity, whereby they have made a commitment to their ethnicity without extensive exploration of the meaning of belonging to their ethnic group. Gender and socio-economic background have significant effects on strength of ethnic identity but not Chinese-medium education. The findings suggest that the Chinese are moderating their ethnic identity but their positive other-group orientation is far from the level of cultural adaptation that is required for assimilation.